PENERAPAN PEMBELAJARAN DISCOVERY UNTUK MENINGKATKAN KEMAMPUAN PEMAHAMAN MATEMATIS PESERTA DIDIK KELAS X MIA 3 SMA NEGERI 4 PEKANBARU - Nurlayli '; Kartini '; Yenita Roza Roza (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: This research is based on the learning process and the students achievement in learning mathematics in class X MIA 3 of SMAN 4 Pekanbaru, there are 20 of 36 students who achieved the Minimum Mastery Criteria or 55,56% for exponent and logarithm lesson. The type of this research is classroom action research. The purpose of this research is to improve the learning process and increase mathematical understanding by implementing discovery learning. The subject of this research were the students in class X MIA 3 ofSMAN 4 Pekanbaru consist of 16 boys and 20 girls at the first semester of academic year 2014/2015. The instruments of data collection in this research were observation sheets and mathematical understanding tests.The observation sheets were analyzed in qualitative descriptive.The qualitative descriptive showed that there is the improvement of learning process after the action on the first and second cycles. The result showed that there is an increase the mathematical understanding of students with the score N-gain is 0,34 in the first cycle and 0,46 in the second cycle at medium classification. The conclusion of this research is the implementation of discovery learning can increase the mathematical understanding of students in class X MIA 3 of SMAN 4 Pekanbaru in the first semester of academic year 2014/2015. Key Word :Mathematical Understanding Ability, Discovery Learning, Clasroom Action Research